Macrophage Reprogramming via the Modulation of Unfolded Protein Response with siRNA-Loaded Magnetic Nanoparticles in a TAM-like Experimental Model - Annarita D'Urso; Francesca Oltolina; Chiara Borsotti; Maria Prat; Donato Colangelo; Antonia Follenzi (MDPI AG, 2023)
New therapeutic strategies are required in cancer therapy. Considering the prominent role of tumor-associated macrophages (TAMs) in the development and progression of cancer, the re-education of TAMs in the tumor microenvironment (TME) could represent a potential approach for cancer immunotherapy. TAMs display an irregular unfolded protein response (UPR) in their endoplasmic reticulum (ER) to endure environmental stress and ensure anti-cancer immunity. Therefore, nanotechnology could be an attractive tool to modulate the UPR in TAMs, providing an alternative strategy for TAM-targeted repolarization therapy. Herein, we developed and tested polydopamine-coupled magnetite nanoparticles (PDA-MNPs) functionalized with small interfering RNAs (siRNA) to downregulate the protein kinase R (PKR)-like ER kinase (PERK) expression in TAM-like macrophages derived from murine peritoneal exudate (PEMs). After the evaluation of the cytocompatibility, the cellular uptake, and the gene silencing efficiency of PDA-MNPs/siPERK in PEMs, we analyzed their ability to re-polarize in vitro these macrophages from M2 to the M1 inflammatory anti-tumor phenotype. Our results indicate that PDA-MNPs, with their magnetic and immunomodulator features, are cytocompatible and able to re-educate TAMs toward the M1 phenotype by PERK inhibition, a UPR effector contributing to TAM metabolic adaptation. These findings can provide a novel strategy for the development of new tumor immunotherapies in vivo.